Semantic error occurrences in the multimedia communications - Lee, , KW (2005)
Since the introduction of communications technologies from analog communications to digital communications, the communication networks have evolved into the ubiquitous network of Internet that triggers the Information Era. The data transmission covers all types of media from bit stream, text, image, audio to video. To increase the accuracy rate of the communications, the processes of error detection and error correction are carried out over the received data, which is majority-wise in the binary form for nowadays communications. Nevertheless, in this paper we try to discuss on the second error level occurring in the multimedia communications. The first error level is the bit stream; whereas the second error level is an advanced error called as semantic error. The semantic error occurrence is explained corresponding to the type of media. Considering the semantic error occurrence, we can have a protection layer in mining the information from the multimedia communications. It is not only applicable to the digital media in the Silicon World, but the daily physical media as well. Hence, we can avoid the critical errors in addition to the higher accuracy rate during the intake process of information. It is highly useful in the field of science, commerce, history, archaeology, etc.